Comparative evaluation of insertion characteristics of PLMA using different techniques in the pediatric age group - Suman Tiwari; Anita Seth (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: The laryngeal mask airway ProSeal (PLMA) insertion should be easy, fast, and atraumatic. Most studies have been done on adults who cannot be considered as the reflection of pediatric patients. In this study, we compared the first attempt success rate of three techniques of PLMA insertion: introducer, 90° rotation, and pharyngoscopy technique in the pediatric population. Material and Methods: In this prospective comparative randomized study, a total of 135 patients of American Society of Anesthesiology grade I and II, aged three to eleven years, with normal airways scheduled for elective surgery, were randomly allocated into three groups: introducer, 90° rotation, and pharyngoscopy group. Parameters evaluated were: first attempt insertion success rate, insertion time, ease of insertion score, hemodynamic parameters, oropharyngeal seal pressure, manipulations, PLMA blood staining, postoperative sore throat, and hoarseness. Results: First attempt insertion success rate was higher in the 90° rotation (97.78%) and pharyngoscopy (97.78%) group as compared to the introducer group (93.33%). But the result was not statistically significant. PLMA insertion time was the least in the rotation group, followed by the pharyngoscopy and introducer group (P < 0.0001). Mean arterial pressure and heart rate were significantly raised in the pharyngoscopy versus rotation group and the introducer versus 90° rotation group after PLMA insertion. Oropharyngeal seal pressure was significantly higher in the introducer as compared to the rotation group (P = 0.007). Conclusion: All three techniques had a high first-attempt insertion success rate. As the rotation technique had the best result in insertion time and hemodynamic response, it may be considered a good alternative to pharyngoscopy and introducer technique in pediatric patients of age three to eleven years with a normal airway. Key Messages: Several studies on PLMA insertion technique in adults are present, but few in the pediatric population. Introducer, pharyngoscopy, and 90° rotation technique were compared. The rotation technique was better in terms of insertion time and hemodynamic stability.